2016
DOI: 10.4103/0974-1208.183509
|View full text |Cite
|
Sign up to set email alerts
|

Effect of myomectomy on endometrial cavity: A prospective study of 51 cases

Abstract: CONTEXT:Fibroids are the most common tumors of the uterine cavity. Most of them are diagnosed during the reproductive age when the fertility is an important concern for the female. However, complications can occur after removal of fibroid (myomectomy) too for future pregnancy. Though myomectomy has been sighted as a cause of intrauterine adhesions data regarding the effect of myomectomy on endometrial cavity is lacking.AIMS:Evaluate the incidence of intrauterine adhesion formation after myomectomy and to ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 21 publications
2
19
1
1
Order By: Relevance
“…One patient developed a broad ligament hematoma, two developed postoperative fever, and one underwent open subtotal hysterectomy 9 hours after surgery for dilutional coagulopathy. Authors concluded that myomectomy for very large fibroids by laparoscopy is a safe alternative to laparotomy for very large myomas [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…One patient developed a broad ligament hematoma, two developed postoperative fever, and one underwent open subtotal hysterectomy 9 hours after surgery for dilutional coagulopathy. Authors concluded that myomectomy for very large fibroids by laparoscopy is a safe alternative to laparotomy for very large myomas [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…In addition, Bhandari et al [13] reported that, most of the participants [72.55%] were cases of primary infertility.…”
Section: Discussionmentioning
confidence: 99%
“…Bhandari et al [13] reported that, of the 50 patients underwent myomectomy, intrauterine adhesions were observed in consequent hysteroscopy in 11 cases [21.57%]. They added, of these 11 adhesion cases, mild adhesions were noted in seven cases, while moderate adhesions were present in three cases.…”
Section: Discussionmentioning
confidence: 99%
“…Myomectomy would result in uterine scarring and synechiae further worsening the subfertility. This can be ruled out through hysteroscopy which is useful for diagnosis and treatment of the intrauterine adhesions [15]. One of our clients had undergone two previous myomectomies and was found to have an endometrial polyp which was hysteroscopically resected after which she was able to conceive through ART.…”
Section: Discussionmentioning
confidence: 99%